2012
DOI: 10.3164/jcbn.11-07
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetic effects of lactic acid bacteria in normal and type 2 diabetic mice

Abstract: The antidiabetic effects of lactic acid bacteria were investigated using mice. In Experiment 1, normal ICR mice were loaded with sucrose or starch with or without viable Lactobacillus rhamnosus GG cells. GG significantly inhibited postprandial blood glucose levels when administered with sucrose or starch. In Experiment 2, KK-Ay mice, a model of genetic type 2 diabetes, were given a basal diet containing viable GG cells or viable Lactobacillus delbrueckii subsp. bulgaricus cells for 6 weeks. Viable GG cells sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 28 publications
(22 reference statements)
3
68
0
1
Order By: Relevance
“…They, eventually, found that only viable L . rhamnosus GG suppressed the elevated FPG in both groups ( p < 0.05) . Concerning the effects of different bacterial strain, El‐Khamisy et al .…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…They, eventually, found that only viable L . rhamnosus GG suppressed the elevated FPG in both groups ( p < 0.05) . Concerning the effects of different bacterial strain, El‐Khamisy et al .…”
Section: Resultsmentioning
confidence: 88%
“…Ultimately, 33 articles were included in the final analysis, consisting of five human and 28 animal reports . Information on human and animal studies in relation to methodological quality, characteristics of participants, interventions and outcome measures are summarized in Tables and .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in future, the partially purified EPS from L. plantarum YML009 could be of use in various clinical therapies for the treatment of various chronic diseases such as cancer and diabetes as also evident by others. 35,36 Research can also be elaborated on human trials since most of the LAB based compounds are known as GRAS. Hence, this partially purified may also prove its usefulness in drug discovery sector.…”
Section: Total Phenolic Contentmentioning
confidence: 99%